A new manual Steering torque estimation model for steer-by-wire systems. (June 2016) - Kim, Seong Han; Chu, Chong Nam
This study proposed a new model to estimate the manual steering torque of steer-by-wire systems. The current steer-by-wire system uses the steering-actuator torque at the end of the rack-and-pinion gear to obtain the manual steering torque. However, there is a need for a new method to obtain the manual steering torque because a steer-by-wire system is expected to develop as it eliminates or at least simplifies more mechanical parts in order to enable them to be combined with other technologies such as an in-wheel motor. In order to propose a new estimation model, this study employs vehicle dynamics modeling and steering-system modeling. Vehicle dynamics modeling is used to estimate the self-aligning moment that arises between the tires and the ground. The slip angle and the normal force, as well as the tire properties of the vehicle, were considered to obtain the self-aligning moment. In addition, the steering system was also considered in this study because the calculated self-aligning moment is transferred through the steering system. The universal joint, the rack-and-pinion gear, and the lower-body linkages were modeled to calculate the manual steering torque delivered to the driver's hands. For validation of the new model, there are two sets of simulation and verification processes in this study. First, the steering-system model was verified through experiments. A steering system was set as the target system, and its mechanical characteristics such as the inertial coefficient, the damping coefficient, and the stiffness were adopted for modeling and verification. Second, the manual steering torque estimation model was verified using field tests. A vehicle was set as the target vehicle, and its specifications such as the dimensions, the steering system, and the lower-body linkages were adopted for modeling and verification. The verification results were presented and show accurate estimation results. The new model proposed in this study does not need mechanical parts to estimate the manual steering torque apart from the steering actuator and the steering feedback actuator and, therefore, it can contribute to the development of a steer-by-wire system.